GAMBARAN PERILAKU SADAR GIZI PADA KELUARGA YANG MEMILIKI BALITA GIZI KURANG DAN GIZI BURUK DI WILAYAH KERJA PUSKESMAS DESA LALANG - Ranika Harahap; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT A good conditional nutrition is a prerequisite to make quality human power. Children with nutrition problem when under old the growth and development of them would be problematic and increase morbidity, decrease productivity and mortality. One of efforts for increase public nutrition status with the way increase nutrition public service by program nutritional family awereness (KADARZI). The purpose of the research is to know the description of nutritional family awarness behavior in under five children that undernutrition in Puskesmas Desa Lalang. This was a descriptive research by survey type. The population in this study was 43 under five children undernutrition of 1-5 years old and all of them were used as the samples. The result of the research was not found of family’s are nutritional family awereness (KADARZI). Based of indicator KADARZI found that family do child weighing (68%), nothing of administering exclusive breast feeding, consumption of combine food (41,9%), used of iodine salt (9,3%), and administering vitamin A capsule (74,4%). The solution for this problem are increase sosialitation and promotion program KADARZI, there are the best mission the nutrition personnel (TPG) and cadre of posyandu (integrated service post), and must make an increased associated for family to KADARZI, especially family with under five children that undernutrition. Keywords : nutritional family awereness (KADARZI), children under five, undernutrition.